Effect of SiO2 on the Performance of Cellulose/Poly(Vinylidene Fluoride) Films as Polymer Electrolytes for Lithium Ion Battery - Shirin Mohamadzade; Seyedeh‐Arefeh Safavi‐Mirmahalleh; Hossein Roghani‐Mamaqani; Mehdi Salami‐Kalajahi (ChemElectroChem)
Abstract Polymer electrolytes serve as highly efficient alternatives to liquid electrolytes, especially in terms of safety in lithium ion batteries. Among various polymers, Cellulose contains electron‐donating atoms which can coordinate with lithium salts and be used as polymer electrolyte. Also, cellulose can be blended with other polymers to improve their properties. Polymer electrolytes suffer from poor mechanical properties. Adding nanoparticles not only surmounts the drawback of poor mechanical properties but also improves physical and electrochemical properties. In this study, different weight ratios of PVDF/cellulose blend films containing silicon dioxide (SiO2) are prepared via solution casting method. The results explored ionic conductivity in order of 10−4 S cm−1. In addition, high transfer numbers (0.74<t+<0.98), wide electrochemical window (up to 6 V), acceptable charge capacity, and long cycle stability are attained. In details, for 90/10 (wt./wt.) cellulose/PVDF, the ionic conductivity reached 4.4×10−⁴ S cm−1, and the ion transfer number was obtained 0.98. Additionally, the electrochemical stability window for these gel polymer electrolytes exceeded 5 V. The sample containing 90 % cellulose achieved an optimal charge capacity of 225.3, with 93.4 % capacity retention after 200 cycles at 0.2 C.